Analysis of Financial Literacy of Economics Teacher Prospectives in the 4.0 Era in Relation to Sustainable Human Resource Formation - Pujiati, Pujiati; Nurdin, Nurdin; Rahmawati, Rahmawati (FKIP Universitas Lampung, 2024)
Financial literacy of prospective teachers in the 4.0 era plays an important role in relation to realizing sustainable human resources. This study aims to determine the influence between the financial literacy of prospective economics teachers in the 4.0 era on the formation of sustainable human resources. This study used quantitative methods. Data was collected by questionnaire dissemination techniques through google forms. The respondents in this study were 188 active student representatives from the classes of 2019, 2020, 2021, and 2022 in students of the economic education study program FKIP University of Lampung. The data were analyzed in a quantitative descriptive. The results of this study show that the financial literacy of prospective economics teachers in the 4.0 era is related to the formation of sustainable human resources. This is proven by a simple linear regression analysis with a significance value of 0.000 < 0.05 which means that the financial literacy of prospective economics teachers in the 4.0 era has a significant effect on sustainable human resource development with an influence of 71.1% and 28.9% influence by other factors that were not studied in this study. Research recommendations should be that higher education institutions can massively foster integrated financial literacy in learning and provide contextual experiences such as the practice of investing through the capital market, saving, and using several financial applications related to financial transactions in everyday life.Keywords: Financial Literacy, Sustainable Human Resources FormationDOI: http://dx.doi.org/10.23960/E3J/v7i1.28-33